2008
DOI: 10.1007/s10681-008-9798-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of high amylose content in maize (Zea mays L.) using a triploid endosperm model

Abstract: Traditionally, high amylose starch (HAS) from maize (Zea mays L.) has been mainly used as an ingredient in gum candies and as an adhesive for corrugated cardboard. Two recent advances have increased interest in the use of HAS. The first one has been the development of starch-based biodegradable thermo plastics. Second, high amylose maize is a source of resistant starch (RS), a type of starch that resists digestion. As a food additive, consumers can benefit from added RS since it will lower the glycemic index a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…By introducing a modifier gene or by coupling with isozyme deficiencies related to starch biosynthesis on the base of inactivation of SBEII, additive effects show a more profound meaning on AC in cereal crops (Wu et al, 2009; Jiang et al, 2010b; Asai et al, 2014). …”
Section: Higher Amylose Increase Through Sbeii Isoform Deficiency Witmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing a modifier gene or by coupling with isozyme deficiencies related to starch biosynthesis on the base of inactivation of SBEII, additive effects show a more profound meaning on AC in cereal crops (Wu et al, 2009; Jiang et al, 2010b; Asai et al, 2014). …”
Section: Higher Amylose Increase Through Sbeii Isoform Deficiency Witmentioning
confidence: 99%
“…When an unknown number of high-amylose modifier (HAM) gene is introduced into a homozygous ae -mutant background in maize, AC is further increased (Wu et al, 2009). The commercial maize GEMS-0067, which is the highest known AC-contained line (>85%), is derived from the predigree of [GUAT209:S13 × (OH43ae × H99ae)] (Li et al, 2008; Wu et al, 2009).…”
Section: Higher Amylose Increase Through Sbeii Isoform Deficiency Witmentioning
confidence: 99%
“…In Zea mays, α-and β-amylases are important because maize seed is rich in starch, the main reserve substance, which represents 70% of the total grain weight (WU et al, 2009). Common maize starch is a mixture of approximately 28% amylose and 72% amylopectin.…”
Section: A Lopes Et Almentioning
confidence: 99%
“…Amylose content is much higher in maize endosperm possessing the ae alleles, which are single recessive endosperm mutant alleles (Fisher et al, 1996;Kim et al, 1998). Wu et al (2009) found that the amylose content of a maize ae homozygote, possessing the modified gene, was elevated by 50-80%, relative to a cultivar without the modified gene.…”
Section: Introductionmentioning
confidence: 99%
“…Maize grain is high in starch, amounting to 70% of the total weight of grain (Wu et al, 2009). Common maize starch is a mixture of approximately 28% amylose and 72% amylopectin.…”
Section: Introductionmentioning
confidence: 99%